TEACHINGS ON HUMAN HEALTH AND NATURE USING THE HERITAGE OF ABU ALI IBN SINA - Umirzaqova Gulmira Egamberdi qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, it is emphasized that the use of Abu Ali ibn Sina's views on the systematic topics included in the curriculum of biology lessons will give effective results, and as a result of the formation of knowledge about nature and human health, the issues of responsible attitude to the environment and nature in their education are highlighted.